Hypersensitivity and nephelauxetic effect of Er3+ in bismuth tellurite glass system - Muhammad Noorazlan Abd Azis (Tanjung Malim, 2023)
Hypersensitivity and nephelauxetic effect of Er3+ in bismuth tellurite glass system by Muhammad Noorazlan Abd Azis